GIEE 2011 : gender and interdisciplinary education for engineers : formation interdisciplinaire des ingénieurs et problème du genre - Beraud, André; Godfroy, Anne-Sophie; Michel, Jean (SensePublishers, 2012)
Attracting more young people, particularly women, in Engineering and Technology (ET) is a major concern in Europe today. Their participation in engineering occupations appears to be a key-issue for European economic and technical development, as well as a central achievement towards gender equality and social justice. Increasing young people's interest in the sciences and mathematics and underlining the importance of Engineering and Technology developments in shaping our collective future is an ongoing project in the education sector. This book presents various analyses and ideas for possible solutions. Aujourd'hui, attirer plus de jeunes et en particulier des jeunes femmes dans les formations d'ingénieurs est un souci majeur en Europe. C'est une clé pour aller vers l'égalité des sexes et favoriser le développement économique, scientifi que et technologique de l'Europe. Accroitre l'intérêt des jeunes pour les sciences et la technologie est essentiel pour notre futur collectif et constitue un défi majeur pour l'éducation. Ce livre présente des analyses et des idées pour de possibles solutions.